PHYTOCHEMICAL PROFILING AND EVALUATION OF PHARMACOLOGICAL ACTIVITIES OF TRIBULUS TERRESTRIS (LINN.)SEED - VINODHINI S,; DEVI RAJESWARI V, (International Journal of Pharma and Bio Sciences, 2016)
Diabetes mellitus is a metabolic disease characterized by chronic hyperglycaemia generally associated with oxidative stress. The objective of this study is to screen the phytochemical constituents of the seeds of the medicinal plant Tribulus terrestris and to obtain preliminary in vitro data about its antioxidant, antidiabetic and anti-inflammatory activity effects. The in vitro antioxidant activity was assessed for T.terrestris seeds; extracts with different solvents such as methanol, ethyl acetate and chloroform were investigated. Antioxidant activity was measured with three methods, 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, Hydrogen peroxidation and Total antioxidant activity. Each extract exhibits a dose-dependent free radical scavenging action against DPPH, hydrogen peroxidation and total antioxidant, but exhibits diverse antioxidant activities. To determine the antidiabetic activity, each extracts were analysed the assays of glucose uptake, α-amylase and glucose diffusion and anti-inflammatory activity was performed. The results show that methanolic extract have an effective activities when compared to ethyl acetate and chloroform extracts. Hence, methanolic extract of T.terrestris possess higher antioxidant, antidiabetic and anti-inflammatory activity, while compared to ethyl acetate and chloroform extract. The compounds were separated by thin layer chromatography. Intervention studies are essential to provide confirmation for a safe and effective use of the identified medicinal plants in the treatment. The present study shows that the methanolic extract of T.terrestris act as a potent antioxidant, antidiabetic activity and anti-inflammatory activity.